2023
DOI: 10.1136/svn-2023-002380
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery for haemorrhagic cerebral cavernous malformation: a multi-institutional, retrospective study

Abstract: BackgroundCerebral cavernous malformations (CCMs) frequently manifest with haemorrhages. Stereotactic radiosurgery (SRS) has been employed for CCM not suitable for resection. Its effect on reducing haemorrhage risk is still controversial. The aim of this study was to expand on the safety and efficacy of SRS for haemorrhagic CCM.MethodsThis retrospective multicentric study included CCM with at least one haemorrhage treated with single-session SRS. The annual haemorrhagic rate (AHR) was calculated before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…In univariate Cox analysis, patients treated with a margin dose >13Gy were more likely to bleed after SRS (HR: 2.57 (95% CI= (1.03-6.45), p=0.044), a recent observation. This result replicated one previous study which included part of this population with hemorrhagic CCMs irrespective of their location 12 . One potential explanation is that high radiation doses induce overexpression of VEGF, leading to neovascularization and subsequent bleeding.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In univariate Cox analysis, patients treated with a margin dose >13Gy were more likely to bleed after SRS (HR: 2.57 (95% CI= (1.03-6.45), p=0.044), a recent observation. This result replicated one previous study which included part of this population with hemorrhagic CCMs irrespective of their location 12 . One potential explanation is that high radiation doses induce overexpression of VEGF, leading to neovascularization and subsequent bleeding.…”
Section: Discussionsupporting
confidence: 90%
“…Volumetric changes were categorized based on pre-speci ed cutoff points: increase with enlargement by more than 20%, decrease with volumetric reduction exceeding 20% of baseline volume, and stable otherwise. 12…”
Section: Study Endpoints and Follow-upmentioning
confidence: 99%
“…Post-radiosurgery AHR tends to decrease in most radiosurgery reports, especially after the initial 2 years [15,[18][19][20][21][22][23]. Factors associated with a higher risk of postradiosurgery hemorrhage include deep CCMs [24,25], pre-treatment hemorrhage [22,24,25], female gender [25], DVA presence [26], younger age [24], larger volume [18,22], and margin doses below 20 Gy [13] or 13 Gy [27]. However, conflicting findings have been reported.…”
Section: Pre-and Post-radiosurgery Hemorrhagementioning
confidence: 99%
“…However, conflicting findings have been reported. For instance, Liscák et al [27] highlighted the relationship between maximum dose and rebleeding [28,29], while Dumot et al [26] suggested that margin doses exceeding 13 Gy could elevate the risk of post-radiosurgery hemorrhage. Dose variations have been observed across different lesions and studies.…”
Section: Pre-and Post-radiosurgery Hemorrhagementioning
confidence: 99%
See 1 more Smart Citation